From narcosis to recovery: development of a rapid diagnostic test for phosphine resistance - Athanassiou, Christos G.; Kavallieratos, N. G.; Brabec, Daniel L.; Oppert, B.; Guedes, Raul Narciso C.; Campbell, James F. (Julius-Kühn-Archiv, 2018)
Hydrogen phosphide (PH3) is the most commonly used gas for insect control in durable stored products. One of the quick diagnostic tests that are currently in use is the Detia Degesch Phosphine Tolerance Test Kit (DDPTTK), which has been developed by Detia Degesch GmbH (Laudenbach, Germany). DDPTTK provides a rapid evaluation tool for phosphine resistance, where insects are exposed in syringes that contain a high concentration of gas (e.g. 3000 ppm), while this gas is produced on site by adding tablets into a canister. We used DDPTTK to evaluate resistance of the red flour beetle, Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) to phosphine. For this purpose, we followed a specific succession of observations on the exposed adults of this species, in an effort to set the scene for designing a rapid diagnostic tool for phosphine resistance, based upon quick bioassays. Two T. castaneum strains were used, one susceptible and one resistant to phosphine. Twenty adults of each of the populations (separate sets of adults each time) were placed in syringe of 100 ml under 1000 or 3000 ppm of phosphine. The insects inside the syringe were monitored at 15-min intervals, for a total period of 90 min, and classified as active, under narcosis and immobilized. After this period, all insects were removed from the syringe and placed in plastic petri dishes with a small quantity of wheat flour. The insects were classified again at the three categories above, after 2 h, 1 d, 2 d, 3 d and 7 d. Regarding the exposure period, at 1000 ppm, all adults of the susceptible strain were immobilized after 60 min of exposure, and remained at this condition until the end of the observation period. At the same concentration, the majority of adults of the resistant strain remained active until the end of the observation period. At 3000 ppm, for the susceptible strain, all adults became immobilized after 90 min observation. For the same concentration, the percentage of the adults of the resistant strain that were active was notably reduced in comparison with 1000 ppm. For the post-exposure period, at 1000 or 3000 ppm, for the susceptible strain, the number of adults that were immobilized reached 95 % after 7 d. At the same phosphine concentration, almost all of the adults of the resistant strain were active even at the 2 h post-exposure period, and practically remain at this condition until the end of the observation period. Our findings indicate that time-to-narcosis / immobilization is inversely proportional to time-to-recovery of the same individuals, and this characteristic can be also considered as an indicator for resistance.